Ajaran Syaikh Khusaeri Hikmatullah “Si Wali Kutub” Tentang PuasaDi Kota Jawa Tengah - A.M Wibowo (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
Sect Khusaeri Hikmatullah is one of sect that use Islam as their symbol.He claims his self as “walikutub” (leader of wali). There is different in thissect with Islam that publicy known. The difference is in Ramadhan determi-nation. In determining compulsory fasting for its follower this sect utilizescalendar syamsiah (Masehi) not qamariah as as conducted by muslim ingeneral.This is qualitative research by using case study approach. Data Source inthis research this is famili’s Khusaeri in Pekalongan city, followers, religiousfgure especially chief of branch NU of Kelurahan Duwet, and society aroundKelurahan Duwet. This study used interview and information documenter.Qualitative descriptive analysis fnding of this research depicts that to de-termine the compulsory fasting every year this sect decided june 1 st as thefrst day for compulsory fasting and july 1 st as idul ftri (lebaran day) eachyear.Key Words : Sect, Fasting, Ramadhan, June, July, Idul Fitri